2019
DOI: 10.3390/aerospace6020018
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Aspects of Creating Low-Curvature Panels for Prospective Civil Aircraft

Abstract: For this study, structural and manufacturing schemes for low-curvature pressurized fuselage panels were proposed, making it possible to provide high weight efficiency for the airframes of prospective civil blended wing-body (BWB) aircraft. The manufacturing scheme for low-curvature panels helped to achieve high strength characteristics of the composite details as well as decreased the labor input necessary for manufacturing and assembling. The beneficial features of the proposed structure are that the panels h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Work by Rahman and Whidborne [6] has shown that a feedback loop is needed for enhanced lateral stability due to the oscillation and the damping factor of the Dutch roll mode. Apart from the potential flying and handling qualities issues, the BWB concept is also challenged with regards to its weight efficiency [7]. In theory, flying wings can be designed to be inherently stable [8] and there have been 'flying wings' that have flown successfully; an example of this being the Northrop YB-49.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Rahman and Whidborne [6] has shown that a feedback loop is needed for enhanced lateral stability due to the oscillation and the damping factor of the Dutch roll mode. Apart from the potential flying and handling qualities issues, the BWB concept is also challenged with regards to its weight efficiency [7]. In theory, flying wings can be designed to be inherently stable [8] and there have been 'flying wings' that have flown successfully; an example of this being the Northrop YB-49.…”
Section: Introductionmentioning
confidence: 99%
“…This design follows very similar characteristics to that of the 'flying wing', including th e downside that, without a horizontal stabiliser, the aircraft is liable to longitudinal instability, which is a phenomenon that has been reported for various prototypes and studies (Okonkwo and Smith, 2016). Apart from the potential flying and handling qualities issues, the BWB concept is also challenged with regards to its weight efficiency (Dubovikov et al, 2019). In theory, flying wings can be designed to be inherently stable (Karl and Wohlfahrt, 1994) and there have been 'flying wings' that have flown successfully; an example of this being the Northrop YB-49.…”
Section: Introductionmentioning
confidence: 94%
“…Porous materials are a class of substances that contain numerous interconnected or enclosed pores or voids inside, with the key features of high porosity, low density, large specific surface area, and high specific strength. These characteristics contribute to their lightweight, good sound and heat insulation, high permeability, and energy adsorption capacity, making porous materials suitable for widespread applications in aerospace, automotive, construction, and other industries [1][2][3]. The development of porous materials has therefore become an active area of research, with scientists exploring new methods to prepare and modify porous materials with desired properties for specific applications.…”
Section: Introductionmentioning
confidence: 99%